Development and theoretical substantiation of technology of formation of information and digital competence of medical students vocational colleges - Nataliia Iukhno (Kazimierz Wielki University, 2020)
The article is devoted to the problem of formation of information and digital competence of students of medical vocational colleges. The scientific analysis of the content of the concepts "information and digital competence" is carried out. The components of information and digital competence of students of medical vocational colleges are determined. Criteria (motivational, cognitive-informational, procedural, reflective-effective), indicators (motives, needs, interests that motivate the formation of information and digital competence of students of medical vocational colleges; positive attitude of students to the formation of information and digital competence; desire to use ICT training in the process of occupational practice, understanding the role of information and prospects for the use of ICT in medicine, knowledge of basic concepts related to ICT training, information and digital tools in educational and professional activities, a set of skills needed by a medical vocational college student to search, transmission and storage of information, the ability to adequately assess their own activities using ICT training in medicine, control, self-control, evaluation and self-evaluation of the process and results of activities for further reassessment) and the level of readiness of information and digital competence of students of medical vocational colleges (high, medium, low). The technology of formation of information-digital competence of students of medical vocational colleges, which includes motivational-target, cognitive-activity, reflection-corrective stages, is scientifically substantiated and developed. The effectiveness of the technology is ensured by the following didactic conditions: actualization of motivational and value training of medical vocational college students; organization of interaction of students and teachers of medical vocational colleges on the Internet through the creation of information and digital learning environment based on individual student support; creation of individual educational routes of students during training and occupational practices.